Biomedical Potential of Nanotechnology: A Review of Emerging Applications and Future Prospects - Kumar, Pankaj; Singh, Kamaljeet; Singh, Lakhwinder; Singh, Jagmeet; Gupta, Sahil (Far Western Review, 2024)
Nanotechnology is an emerging field that covers a wide range of technologies that are presently under development at the nanoscale. It plays a major role in the development of innovative methods to produce new products, to substitute existing production equipment, and to reformulate new materials and chemicals with improved performance, resulting in less consumption of energy and materials and reduced harm to the environment as well as environmental remediation. The ability to investigate substances at the molecular level has boosted the search for materials with outstanding properties for use in medicine. The application of these novel materials has generated the new research field of nanobiotechnology, which plays a central role in disease diagnosis, drug design and delivery, and implants. In this review, we provide an overview of the use of metallic and metal oxide nanoparticles (MONPs), carbon-nanotubes (CNTs), liposomes, and nanopatterned flat surfaces for specific biomedical applications. The chemical and physical properties of the surface of these materials allow their use in diagnosis, biosensing and bioimaging devices, drug delivery systems, and bone substitute implants. The toxicology of these particles is also discussed in the light of a new field referred to as nanotoxicology that studies the surface effects emerging from nanostructures materials.